2014
DOI: 10.1371/journal.pone.0111498
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multimorbidity on Disability and Quality of Life in the Spanish Older Population

Abstract: BackgroundPopulation aging is closely related to high prevalence of chronic conditions in developed countries. In this context, health care policies aim to increase life span cost-effectively while maintaining quality of life and functional ability. There is still, however, a need for further understanding of how chronic conditions affect these health aspects. The aim of this paper is to assess the individual and combined impact of chronic physical and mental conditions on quality of life and disability in Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
122
4
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 82 publications
21
122
4
5
Order By: Relevance
“…This result is consistent across studies that consider only a limited number of chronic conditions, some as low as 11 conditions [11], and those that incorporate a larger number of chronic conditions, one incorporating as high as 45 conditions [12]. The latter study which also derives weighted counts showed that severity should be an important consideration in HRQoL studies among those with multimorbidity.…”
Section: Short Communicationsupporting
confidence: 73%
See 4 more Smart Citations
“…This result is consistent across studies that consider only a limited number of chronic conditions, some as low as 11 conditions [11], and those that incorporate a larger number of chronic conditions, one incorporating as high as 45 conditions [12]. The latter study which also derives weighted counts showed that severity should be an important consideration in HRQoL studies among those with multimorbidity.…”
Section: Short Communicationsupporting
confidence: 73%
“…A second study that considered synergistic effects in a different set of two pairs of conditions found that the combined worsening effect of the first pair (diabetes and cataract) on HRQoL was barely significant [11]. In contrast, the combined effect of the second pair (asthma and COPD) in this study was significant but implied a dampening effect on HRQoL.…”
Section: Short Communicationcontrasting
confidence: 72%
See 3 more Smart Citations